Sequence analysis of ribosomal protein gene, L14 in human colorectal carcinoma cell line - Najian, binti Ibrahim (Universiti Malaysia Sarawak (UNIMAS), 2015)
Structural information of ribosomal proteins (RPs) has increased the understanding of the structure, function and evolution of the ribosome. RPL 14 is one of the most conserved ribosomal proteins and have a major role in the ribonucleoprotein complex. Previous investigations have revealed that RPs gene expression in colorectal carcinomas (CRC) differs from that was found in normal colorectal cells; some are upregulated and some are down regulated. It has been inferred that the unregulated expression of RPs are associated with the differentiation, progression or metastasis of CRC. This project analyses one of the RP genes, RPL 14 which is taken from colorectal cancer cells. Analysis shown that RPL 14 gene extracted has not undergo any mutation as the nucleotide sequence reflects 99% identity from the sequence in Genbank. Besides that, translation result of RPL 14 illustrated that RPL 14 gene encodes a few biologically important sites such as phosphorylations sites for many protein kinases, myristoylation site, and leucine zipper pattern which makes RPL 14 one of the common housekeeping genes in human.